2010
DOI: 10.1097/pcc.0b013e3181b0123b
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive ventilation and low-flow veno-venous extracorporeal carbon dioxide removal as a bridge to lung transplantation in a child with refractory hypercapnic respiratory failure due to bronchiolitis obliterans*

Abstract: Noninvasive mechanical ventilation and Decapsmart have proven efficacious in managing refractory hypercapnic respiratory failure in a pediatric patient awaiting lung transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…The impact of lung alveoli recruitment on PVRs has to be taken in close consideration in LTx candidates, since irreversible PH and tricuspid regurgitation can indicate combined heart-lung transplantation. [16][17][18] Cardiac function was assessed as completely normal after LTx, confirming our impression of a functional problem instead of a structural one (e.g., endocarditis, cardiomyopathy). [5] LCH recurrence in the transplanted organ has not been reported in children, making LTx a true opportunity of increased survival for such patients.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The impact of lung alveoli recruitment on PVRs has to be taken in close consideration in LTx candidates, since irreversible PH and tricuspid regurgitation can indicate combined heart-lung transplantation. [16][17][18] Cardiac function was assessed as completely normal after LTx, confirming our impression of a functional problem instead of a structural one (e.g., endocarditis, cardiomyopathy). [5] LCH recurrence in the transplanted organ has not been reported in children, making LTx a true opportunity of increased survival for such patients.…”
Section: Discussionsupporting
confidence: 58%
“…A better clearance of secretions through the tracheotomy tube, in conjunction with PPV at resting settings, allowed a significant improvement of the echocardiographic signs of PH and right heart failure. The impact of lung alveoli recruitment on PVRs has to be taken in close consideration in LTx candidates, since irreversible PH and tricuspid regurgitation can indicate combined heart–lung transplantation . Cardiac function was assessed as completely normal after LTx, confirming our impression of a functional problem instead of a structural one (e.g., endocarditis, cardiomyopathy) .…”
Section: Discussionmentioning
confidence: 74%
“…-Via T. Caruto, 9-84131 Salerno, Italy) 16,40 and Hemolung (Alung Technologies Pittsburgh, PA) 15 are pump-driven veno-venous systems for PECCO 2 R. Numerous studies showed their effectiveness in reducing CO 2 levels and correcting respiratory acidosis. -Via T. Caruto, 9-84131 Salerno, Italy) 16,40 and Hemolung (Alung Technologies Pittsburgh, PA) 15 are pump-driven veno-venous systems for PECCO 2 R. Numerous studies showed their effectiveness in reducing CO 2 levels and correcting respiratory acidosis.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, smaller membrane lungs can be used (0.3 to 1.35 m 2 ) with lower flow rates (<500 ml.minute -1 ) than conventional ECCOR [33], resulting in similar anticoagulation requirements to continuous venovenous hemodialysis [46]. The Decap has been successfully used in adults and children [9,47,48]. …”
Section: Venovenous Carbon Dioxide Removalmentioning
confidence: 99%